Analisis Postur Kerja Pada Aktivitas Menyetrika di Industri Jasa Laundry Cio’ta Dengan Menggunakan Metode REBA (Rapid Entire Body Assessment) - Dewi, Nurmala; Annas, Fayyadh; Sari, Tria Atika; Budiharjo, Budiharjo (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Ironing activities in the laundry service industry are performed repeatedly and for long periods, creating a high potential for non-ergonomic work postures. At Laundry Cio’ta, ironing is carried out every day from 08:00 to 21:00 by two workers, which increases the risk of fatigue and musculoskeletal disorders due to continuous and repetitive movements. This study aims to analyze workers’ ironing postures using the REBA method to determine the level of ergonomic risk. Data were collected through direct observation and measurement of body posture angles during the ironing process. The assessment results showed a Score A of 4 and a Score B of 2, producing an initial REBA score of 4. With the addition of an activity score of +1, considering the repetitive nature of the task, the final REBA score increased to 5. This score indicates a moderate level of risk, suggesting that corrective actions are necessary to prevent long-term strain or injury. Based on these findings, ergonomic improvements such as adjusting the ironing table height, modifying the work layout, and encouraging workers to adopt better posture are recommended. Implementing short rest breaks and task variation can also help reduce physical strain and improve worker comfort and productivity.